Chronic Ethanol Exposure Disrupts Lactate and Glucose Homeostasis and Induces Dysfunction of the Astrocyte–Neuron Lactate Shuttle in the Brain. (16th July 2019) - Lindberg, Daniel; Ho, Ada Man Choi; Peyton, Lee; Choi, Doo‐Sup
Abstract : Background: Impairment of monocarboxylate transporter (MCT)‐dependent astrocyte‐neuron lactate transfer disrupts long‐term memory and erases drug‐associated memories in mice. However, few studies have examined how drugs of abuse alter astrocyte‐neuron lactate transfer in neurocircuits related to addiction. This is particularly pertinent for ethanol (EtOH), which has been demonstrated to impair central nervious system (CNS) glucose uptake and significantly alter peripheral levels of glucose, lactate, acetate, and ketones. Methods: We subjected C57BL/6J mice to a chronic intermittent EtOH (CIE) exposure paradigm to investigate how chronic EtOH exposure alters the concentration of glucose and lactate within the serum and CNS during withdrawal. Next, we determine how chronic injections of lactate (1 g/kg, twice daily for 2 weeks) influence central and peripheral glucose and lactate concentrations. Finally, we determine how CIE and chronic lactate injection affect astrocyte‐neuron lactate transfer by analyzing the expression of MCTs. Results: Our results show that CIE induces lasting changes in CNS glucose and lactate concentrations, accompanied by increased expression of MCTs. Interestingly, although chronic lactate injection mimics the effect of EtOH on CNS metabolites, chronic lactate injection is not associated with increased expression of MCTs. Conclusion: CIE increases CNS concentrations of glucose and lactate and augments the expression of MCTs. Although we found that chronic lactate injection mimics EtOH‐induced increases in CNS lactate and glucose, lactate failed to alter the expression of MCTs. This suggests that although lactate may influence the homeostasis of bioenergetic molecules in the CNS, EtOH‐associated increases in lactate are not responsible for increased MCT expression. Abstract : Glucose may be transported into the CNS from the blood or may arise from glycogenolysis within astrocytes. We examined the time course of glucose changes within the periphery and CNS following acute injection of 1.0 g/kg lactate. Acute lactate injection exerted a significant main effect on glucose concentrations across time.